English Redundancies Produced by Public Followers in Social Media through Uncle Clinton’s Space Channel - Amran, Ali; Nasution, Habib Syukri (English Teaching and Linguistics Journal (ETLiJ), 2025)
This qualitative study tries to investigate and figure out why the public followers, Indonesian people who are learning to speak English in tik tok, tend to produce English redundancies This evidence is derived through Uncle’s Clinton Space Channel. Redundancies are unnecessary, repetitious words which may appear before and after the main word. They make your conversation longer, but not better. https://www.engvid.com. In English usage, redundancies is usually defined as the use of two or more words that say the same thing, but we also use the term to refer to any expression in which a modifier’s meaning is contained in the word it modifiers (e,g., early beginnings, merge together, return back, very exhausted, very vital, very urgent and so on. They are redundant since they use more that one words. So the words early, merge, return, exhausted, vital, urgent carry enough meaning. Whether or not they realize, they can easily produce those redundancies when they response the questions in Uncle Clinton’s Space channel.  Redundancy, as what Steven explains that they exist at all levels of language: from phonemes and spelling, words and affixes, through syntax, semantics, and discourse. It exists in the reciprocity of linguistic, kinesic, and situational channels of communication.